2020
DOI: 10.1007/s40201-020-00554-0
|View full text |Cite
|
Sign up to set email alerts
|

Carbide Derived Carbon (CDC) as novel adsorbent for ibuprofen removal from synthetic water and treated sewage effluent

Abstract: Purpose Pharmaceuticals are becoming one of the largest environmental concerns when it comes to the water treatment industry. Increased usage of these chemicals poses a serious risk to ecology and human health due to their leakage into surface waters. In the present study, carbide derived carbon (CDC) was used for the first time as a new adsorbent to remove ibuprofen from synthetic water and wastewater effluent. Methods The morphology, chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 75 publications
4
16
0
Order By: Relevance
“…In addition to the SSE, the correlation coefficient (R 2 ) of each model was analyzed using Equation (21) to better evaluate the best fit.…”
Section: Correlation Coefficient (R 2 )mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the SSE, the correlation coefficient (R 2 ) of each model was analyzed using Equation (21) to better evaluate the best fit.…”
Section: Correlation Coefficient (R 2 )mentioning
confidence: 99%
“…Various studies have reported that the concentrations of ibuprofen in wastewater were usually in the range of ng/L to µg/L (703-1673 µg/L [18], 2500-45,000 ng/L [19], and 0.004-603 µg/L [20]. According to Almanassra et al (2020), carbide-derived carbon (CDC) can be utilized as an adsorbent to remove ibuprofen from deionized water and treated sewage effluent successfully [21]. Guedidi et al (2013) claimed that the surface modification of commercial granular-activated carbon, using hydrogen peroxide as an oxidant, led to the formation of carbonyl groups that aid the adsorption uptake of ibuprofen [22].…”
Section: Introductionmentioning
confidence: 99%
“…The Langmuir-Freundlich or SIPS isotherm provides the best correlation to the experimental equilibrium data values based on the SSE and correlation coefficient (R 2 ) values in Other studies (see Table 4.) for the adsorption of IBU using various adsorbents obtained a wide range of capacities; for carbide derived carbon (Almanassra et al 2020), commercial activated carbon (Guedidi et al 2013) and olive waste cake derived activated carbon (Baccar et al 2012) the IBU adsorption capacities were 367, 160 and 14.4 mg IBU/g adsorbent. Two of the values are very high but they were performed at very acidic pH to optimise the capacity.…”
Section: Equilibrium Studiesmentioning
confidence: 99%
“…In this study, ibuprofen is used as a reference compound to evaluate the performance of activated carbon synthesized from local date stones. Almanassra et al (Almanassra et al 2020) reported that carbide-derived carbon (CDC) can be effectively used as an adsorbent for the removal of ibuprofen from deionized water and treated sewage effluent. Guedidi et al (Guedidi et al 2013) claimed that surface modification of commercial granular activated carbon using hydrogen peroxide as an oxidant, led to the formation of carbonyl groups that aid the adsorption uptake of ibuprofen.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the exceptional surface properties of CDC, it can offer more adsorption sites and provide a higher adsorption capacity of pollutants compared to other adsorbents. As such, CDC has been investigated for the removal of pharmaceuticals, [39,40] phosphate, [41] tetraethylammonium tetrafluoroborate electrolytes, [42] carbon dioxide, [43] acetaldehyde [44] and cytokines. [45] The reported data indicate that CDC could be a promising adsorbent for water treatment applications.…”
Section: Introductionmentioning
confidence: 99%